2023
DOI: 10.1007/s00431-023-04846-z
|View full text |Cite
|
Sign up to set email alerts
|

Ventilator-induced diaphragmatic dysfunction in extremely preterm infants: a pilot ultrasound study

Abstract: Purpose: To investigate the development of diaphragmatic dysfunction in ventilated extremely preterm infants (EPI) using diaphragm ultrasound (DU). Methods: EPI of less than 28 weeks' gestational age who required mechanical ventilation within six hours of birth were included in this prospective, observational study. The DU was performed once a day until four days of life. End-inspiratory and end-expiratory thicknesses of the diaphragm were measured and the diaphragm thickening fraction was calculated.Results: … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 20 publications
(35 reference statements)
0
7
0
Order By: Relevance
“…DA and VIDD have been reported in 41% of adults 47% of children undergoing IMV and has been associated with adverse outcomes 8,10,21,22 . In a recent study with 20 extremely preterm infants, 90% of them were found to have VIDD, however, the incidence of DA was not reported 15 . Moreover, the authors of this study only provided data on TDI and diaphragm thickening fraction (DTF) change but not on TDE change.…”
Section: Discussionmentioning
confidence: 81%
See 3 more Smart Citations
“…DA and VIDD have been reported in 41% of adults 47% of children undergoing IMV and has been associated with adverse outcomes 8,10,21,22 . In a recent study with 20 extremely preterm infants, 90% of them were found to have VIDD, however, the incidence of DA was not reported 15 . Moreover, the authors of this study only provided data on TDI and diaphragm thickening fraction (DTF) change but not on TDE change.…”
Section: Discussionmentioning
confidence: 81%
“…8,10,21,22 In a recent study with 20 extremely preterm infants, 90% of them were found to have VIDD, however, the incidence of DA was not reported. 15 Moreover, the authors of this study only provided data on TDI and diaphragm thickening fraction (DTF) change but not on TDE change. In our experience, and based on pathophysiologic considerations, TDI reflects the individual's ability to contract the diaphragm and is therefore influenced by multiple factors such as sleep state, agitation (and level of sedation), time from last meal, drugs (i.e., caffeine).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In fact, invasive mechanical ventilation (MV) leads to the rapid development of diaphragmatic weakness due to the onset of muscle atrophy and contractile dysfunction. This condition has been defined as ventilator-induced diaphragmatic dysfunction and has been associated with extubation failure [ 48 , 49 ]. Other authors reported that the LUS score but not diaphragmatic excursion parameters could predict extubation failure [ 50 ].…”
Section: Resultsmentioning
confidence: 99%